2020
DOI: 10.1505/146554820828671535
|View full text |Cite
|
Sign up to set email alerts
|

Economic returns to households participating in different models of commercial tree plantations in Lao PDR

Abstract: Four tree plantation models implemented in Lao PDR and a hypothetical model were compared in terms of the projected economic benefits and those realised by participating rural households, and households' attitudes to further plantation expansion. Models comprised two forms of land-sharing plantation concessions, and contract and independent tree growing. Benefits and costs over the plantation cycle were used to calculate net present values. Tree plantations contributed most to household livelihoods when compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Shareholders, donors and investors in plantation companies may require community participation for sustainable investments [72,73]. Timber plantation management models that engage local communities result in the highest economic returns to plantation companies and improve local livelihoods, leading to avoidance of potential conflicts over land [31,32]. Van der Meer Simo et al [32] further found that local households were open to expansion of plantation models that provide beneficial effects to local villagers by incorporating their interests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shareholders, donors and investors in plantation companies may require community participation for sustainable investments [72,73]. Timber plantation management models that engage local communities result in the highest economic returns to plantation companies and improve local livelihoods, leading to avoidance of potential conflicts over land [31,32]. Van der Meer Simo et al [32] further found that local households were open to expansion of plantation models that provide beneficial effects to local villagers by incorporating their interests.…”
Section: Discussionmentioning
confidence: 99%
“…Timber plantation management models that engage local communities result in the highest economic returns to plantation companies and improve local livelihoods, leading to avoidance of potential conflicts over land [31,32]. Van der Meer Simo et al [32] further found that local households were open to expansion of plantation models that provide beneficial effects to local villagers by incorporating their interests. A participatory approach is important because rural households highly depend on land as a source of livelihood and may contest plantation development unless their interests are integrated and recognized in land use and plantation development processes [74,75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While rubber plantations expanded rapidly based on investment from neighboring China, Viet Nam and Thailand, high expectations of abundant and affordable land for timber plantations were generally not met [64]; and plantation investors tried other arrangements to access land, including through contract farming which was promoted in policy, or by leasing land directly from households or villages. Novel arrangements to find enough suitable land emerged, including by integrating commercial timber production with local land uses and agroforestry models [9,65,66]. These were often determined by the corporate values of investors and through Provincial-and District-level interpretations and application of policies and regulations.…”
Section: History Of Policies For Plantations In Laosmentioning
confidence: 99%
“…[41,76,77]). Income from participation in plantations must be considered alongside these other sources of income if a realistic appraisal is to be made of the contribution of plantation forests to rural livelihoods poverty alleviation targets (see [127]). In that context, the value of the environment to local livelihoods should be a central consideration for future studies of plantation forests replacing subsistence agriculture [86,105,128].…”
Section: The Future Role Of Plantation Forests Researchersmentioning
confidence: 99%